The Rheology Quality of Rabbit Meatballs at Subtitutied starch with Sago Flour on Prerigor dan Postrigor Fase - . Farida; E. Abustam; S. Kadir (Jurnal Ilmu dan Teknologi Peternakan, 2014)
The meat of rabbit is one of animal protein sources. Prerigor meat is having a better quality in processing the meat especially for meatballs, however, the availability of this prerigor meat is difficult to obtain. Therefore, the use of postrigor meat could be used with consequently that should be add by a binder such as starch or others binder.  Sago flour was not often used as binder, the present study was conducted to know whether the quality of rabbit meatballs using sago flour as a binder similar of that the meatballs using starch as a binder. The design of this study was completely randomized of factorial pattern 2 x 5 with 3 replications. The first factor was the condition of rigor (prerigor and postrigor), while the second factor was the combination levels between starch and sago flour (30% starch, 30% sago, 15% starch +15 % sago, 20% starch +10% sago and 10% starch +20% sago). The strength of meatballs using compression method, cooking loses, and the microscopic structures of rabbit meatballs were test in the study. The results of this study showed that different rigormortis condition of the meat affected the quality of rabbit meatballs,  in terms of strength, cooking loses, and microscopic structures. The addition of a combination of starch and sago at a different levels influenced the quality of meatballs in terms of strength, and microscopic structures. The best meatballs quality was obtained by using prarigor meat with 15% starch +15% sago flour.